Information transmission in action video gaming experts: Inferences from the lateralized readiness potential - Xie, Jiaxin; Cui, Ruifang; Ma, Weiyi; Lu, Jingqing; Wang, Lin; Ying, Shaofei; Yao, Dezhong; Gong, Diankun; Yan, Guojian; Liu, Tiejun (Frontiers in Human Neuroscience, 2022)
Research showed that action real-time strategy gaming (ARSG) experience is related to cognitive and neural plasticity, including visual selective attention and working memory, executive control, and information processing. This study explored the relationship between ARSG experience and information transmission in the auditory channel. Using an auditory, two-choice, go/no-go task and lateralized readiness potential (LRP) as the index to partial information transmission, this study examined information transmission patterns in ARSG experts and amateurs. Results showed that experts had a higher accuracy rate than amateurs. More importantly, experts had a smaller stimulus-locked LRP component (250 – 450 ms) than amateurs on no-go trials, while the response-locked LRP component (0 – 300 ms) on go trials did not differ between groups. Thus, whereas amateurs used an asynchronous information transmission pattern, experts used a reduced asynchronous information transmission pattern or a synchronous pattern where most of processing occurred prior to response execution – an information transmission pattern that supports rapid, error-free performance. Thus, experts and amateurs may use different information transmission patterns in auditory processing. In addition, the information transmission pattern used by experts is typically observed only after long-term auditory training according to past research (Gong et al., 2013). This study supports the relationship between ARSG experience and the development of information processing patterns.